The Effect of Retaining Bonuses on Delaying Early Retirement – Financial Incentives Revisited - Hermansen, Åsmund; Midtsundstad, Tove (Nordic Journal of Working Life Studies, 2018)
In this paper, we analyze the effect of the retaining bonus on early retirement behavior using a unique dataset consisting of a Norwegian employer survey from 2010 combined with register data on all older employees in the period 2000–2010. The retaining bonus is one of the most common retention measures offered by Norwegian companies to prevent their older workers from retiring early. The most common arrangement is a lump sum of between 10,000 and 25,000 Norwegian Kroner (between 1100 and 2600 Euros), which was less than the mean monthly pay before tax in Norway in 2010. In spite of this modest sum, our analysis shows that retaining bonuses of 20,000 NOK or more do reduce the probability of 61-year-olds retiring in the next two years of employment